MODERN DIAGNOSTIC METHODS FOR IRON DEFICIENCY ANEMIA: FROM CLINICAL PRACTICE TO MOLECULAR RESEARCH - Bo’stonova Raxnamo Alamovna; Isomadinova Lola Kamolidinovna; Karimova Linara Alixanovna; Murotkulov Gayrat Akmal o’g’li (Web of Journals Publishing, 2025)
Iron deficiency anemia (IDA) is one of the most common forms of anemia worldwide. This article explores modern diagnostic methods for IDA, ranging from standard laboratory analyses to molecular research. The importance of integrating various diagnostic approaches to enhance diagnostic accuracy is emphasized.